Development Strategy of Batu Lawang Tourist Attraction as a Leading Tourism Destination in Cirebon Regency - Viollyn Indryani; Dhea Amanda; Islah Oftaviani; Yudi Stiansyah; Harmoko Harmoko (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose : This study aims to explore the importance of tourist attractions in strengthening the tourism sector and its impact on sustainable development in various destinations, with a special focus on Batu Lawang nature tourism in Cirebon. Method: The study used a qualitative approach with descriptive methods, involving in-depth interviews, participant observation, and documentation studies. Results: The study shows that Batu Lawang has uniqueness and great potential in attracting tourists through its natural beauty and various interesting activities, although it still faces obstacles such as infrastructure that needs to be improved and promotion that has not been maximized. The proposed strategies include setting visitor quotas to overcome over-tourism, managing traffic and mobility, maintaining tourist facilities, and developing attractions. Contribution: This study is useful for tourism managers, government, and local communities in efforts to develop and promote Batu Lawang, and provides a basis for further research to support the growth of sustainable tourism in the area.